Successful collaboration in education: the UMeP. (December 2014) - Smith, Laura‐Jane; Belcher, Rosie; Coppola, Will; Gill, Deborah; Spencer, Hilary; Cooper, Chris; Rawlinson, Nigel; Williams, Jane; Haig, Alex; Smith, Joel; Haq, Inam; Jones, Anna; et al.
Summary Background As the health care education landscape in the UK changes rapidly and dramatically, collaboration across institutions bridging undergraduate and postgraduate fields is increasingly necessary. Collaboration entails both risks and benefits. There is a paucity of advice on how to ensure collaborative projects in medical education are effective. <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> There is a paucity of advice on how to ensure collaborative projects in medical education are effective </boxed-text> Context In 2011 three medical schools began a collaborative project along with NHS Education for Scotland (NES) to modify, develop and deliver a medical school version of the NES foundation programme ePortfolio, called UMeP. The underlying principal was the introduction of an authentic ePortfolio early in undergraduate life. The challenge of three diverse medical schools with significantly different curricula and assessment approaches working together with a single postgraduate ePortfolio was complex and demanding. Discussion We reveal the complexities of collaboration on education projects and draw on our experiences to provide illustrative examples of collaboration. Despite the increased complexity and need for compromise, we argue that successful collaborative partnerships are key to maximising the circumstances in which education innovation can be successful, and create the potential for robust evaluation and research.